2023
DOI: 10.1002/chem.202203288
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Liquid Crystals With Close π–π Packing: The Effect of Blatter Radical Planarization on Behavior of Bent‐Core Mesogens

Abstract: A new, 19 π-delocalized electrons planar Blatter radical building block was developed and used to obtain paramagnetic bent-core liquid crystals. The mesogens were investigated by optical, thermal, powder XRD and DFT methods in the pure form and as binary mixtures. Comparison of their properties with those of the classical Blatter radical analogues revealed that planarization of the central angular element results in a significantly higher stability of the mesophases and increased molecular organization suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…For instance, a derivative of Blatter’s radical can be refluxed in chlorobenzene (bp 131 °C) without decomposition and can be heated in the solid phase to ∼270 °C before decomposition begins . Numerous derivatives of the Blatter radical have been recently prepared and their interesting properties studied; this includes DNP agents for NMR spectroscopy, the magnetically ordered thin film of pyrene–Blatter on SiO 2 /Si substrate that is stable at ambient conditions, self-assembled films of Blatter radical on Au, paramagnetic liquid crystals of “planarized” Blatter, , batteries, and potential molecular qubits. , Derivatives of the Blatter radical are important building blocks for thermally robust and ultrarobust high-spin di- and triradicals (sections and ). …”
Section: Persistent and Stable Monoradicals As Spin Centersmentioning
confidence: 99%
“…For instance, a derivative of Blatter’s radical can be refluxed in chlorobenzene (bp 131 °C) without decomposition and can be heated in the solid phase to ∼270 °C before decomposition begins . Numerous derivatives of the Blatter radical have been recently prepared and their interesting properties studied; this includes DNP agents for NMR spectroscopy, the magnetically ordered thin film of pyrene–Blatter on SiO 2 /Si substrate that is stable at ambient conditions, self-assembled films of Blatter radical on Au, paramagnetic liquid crystals of “planarized” Blatter, , batteries, and potential molecular qubits. , Derivatives of the Blatter radical are important building blocks for thermally robust and ultrarobust high-spin di- and triradicals (sections and ). …”
Section: Persistent and Stable Monoradicals As Spin Centersmentioning
confidence: 99%
“…Additionally, Cigl et al synthesized novel bent-core mesogens based on Blatter radicals 52 and planar periannulated Blatter radicals 53 respectively, and studied their different mesogenic behavior in liquid crystalline phases. [147] After exploring liquid crystalline behavior of 52 and 53, it was found that the planarization of 53 causing close molecular packing, higher mesophases stability and tendency to form various types of ordered phases in liquid crystalline phases. This study also revealed potential applications for functional paramagnetic bentcore mesogens.…”
Section: Triazinyl Radicalsmentioning
confidence: 99%
“…Recent advances in the design and synthesis of thermally robust high-spin di- and triradicals based on the Blatter radical have expedited the preparation of organic radical thin films via controlled evaporation under ultrahigh vacuum (UHV). , Notable developments include thin films of an S = 1/2 Blatter radical derivative exhibiting magnetic ordering and a high-spin ( S = 1) Blatter-based diradical with robust stability and electrical conductivity . In addition, robustness and synthetic availability of S = 1/2 Blatter radicals enabled their recent applications as paramagnetic liquid crystals, , batteries, and potential molecular spin qubits . Likely, other novel properties will emerge from the remarkable Blatter radical; however, we are in search of new S = 1/2 building blocks for future development.…”
Section: Introductionmentioning
confidence: 99%